Naphthalene flanked diketopyrrolopyrrole based organic semiconductors for high performance organic field effect transistors - Liu, Q.; Sun, H.; Blaikie, C.; Caporale, C.; Manzhos, S.; Feron, K.; Macleod, J.; Massi, Massimiliano; Bottle, S.; Bell, J.; Noh, Y.; Sonar, P. (Royal Society of Chemistry, 2018)
Here, we design and synthesize three new diketopyrrolopyrrole (DPP) derivatives with naphthalene, possessing large-scaled p-delocalized electronic structure, as the flanking groups and both linear (n-decyl and n-dodecyl) and branched (2-hexyldecyl)alkyl chains as substitutions as active layer for high performance organic field-effect transistors (OFETs). The thermal, photophysical properties, energy levels and solid state molecular stacking have been studied in detail. All the materials show excellent thermal stability with a decomposition temperature of 400 °C, high semi-crystallinity feature, suitable HOMO & LUMO energy levels, and varying crystalline domain sizes in thin films. Bottom-contact/top-gate transistor devices are thus fabricated to investigate the mobility. Encouragingly, all compounds function well in OFET devices and show significant potential as p-type semiconducting materials. The monomer with the n-decyl alkyl chain (D-DPPN) shows the highest mobility of 0.019 cm2V-1s-1, with the Ion/Ioffratio reaching 106. We for the first time synthesize naphthalene flanked DPP monomers and achieve high mobility in OFET devices when using these monomers without any further functionalization as semiconductors directly. The primary result that high mobility is observed for monomers only opens a new way for further DPP application and provides more possibilities for constructing high performance polymeric and small molecular semiconductors based on this new DPP dye.